Peningkatan Kemampuan Membaca Anak Usia Dini 5-6 Tahun Menggunakan Media Cantol Gambar - Nisa', Luthfatun; Hasanah, Faridatul (Absorbent Mind, 2023)
This research aims to describe the effectiveness of picture hook media in improving the reading skills of young children aged 5-6 years by using picture hook media at RA AS-AS-Sholihin. This research uses the Kemmis and Mc classroom action research model. Taggart. This research was carried out in January 2023 for three cycles. The subjects of this research were 18 RA AS-Sholihin group B students. The data collection techniques used are observation, tests, documentation, and interviews. Meanwhile, research instruments use observation sheets, tests, and documentation. The results showed that there was an increase in reading skills in early childhood in the B RA AS-Sholihin group by using hook pictures as media. This increase can be seen from the results of observations which increase in each cycle. The average value obtained in cycle I reached 39%, in cycle II it reached 61%, and in cycle III it reached 89%. The results of this research show that the use of picture hook media can improve children's reading abilities. Based on the statement above, the researcher concluded that the use of hook pictures in As-Sholihin RA was said to be very influential in children's learning processes. Namely by using picture hook media the learning atmosphere is more enjoyable, and children are more interested in learning to read so that it can help improve reading skills.